2015
DOI: 10.1016/j.jplph.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of AOX and UCP pathways in the post-harvest ripening of papaya fruits

Abstract: Enhanced respiration during ripening in climacteric fruits is sometimes associated with an uncoupling between the ATP synthesis and the mitochondrial electron transport chain. While the participation of two energy-dissipating systems, one of which is mediated by the alternative oxidase (AOX) and the other mediated by the uncoupling protein (UCP), has been linked to fruit ripening, the relation between the activation of both mitochondrial uncoupling systems with the transient increase of ethylene synthesis (eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…The relatively high expression of CsAOXa and CSAOXd in fruits (>15 RPKM; Fig 6) may be related to the expression of AOX genes from other species producing fruits such as tomato, papaya or mango [5558]. Some AOX genes were related to fruit maturation, ripening and post-harvest ripening in association with ethylene peak emission (climacteric fruits) [56, 57], while other AOX genes were associated to gametophyte development [58]. Some AOX genes related to climacteric fruit ripening presented elements responsive to ethylene in their promoter sequences [57].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively high expression of CsAOXa and CSAOXd in fruits (>15 RPKM; Fig 6) may be related to the expression of AOX genes from other species producing fruits such as tomato, papaya or mango [5558]. Some AOX genes were related to fruit maturation, ripening and post-harvest ripening in association with ethylene peak emission (climacteric fruits) [56, 57], while other AOX genes were associated to gametophyte development [58]. Some AOX genes related to climacteric fruit ripening presented elements responsive to ethylene in their promoter sequences [57].…”
Section: Resultsmentioning
confidence: 99%
“…Some AOX genes were related to fruit maturation, ripening and post-harvest ripening in association with ethylene peak emission (climacteric fruits) [56, 57], while other AOX genes were associated to gametophyte development [58]. Some AOX genes related to climacteric fruit ripening presented elements responsive to ethylene in their promoter sequences [57]. Here, the CsAOXa and CSAOXd genes did not present any elements responsive to ethylene in their promoter sequences; this could be related to the fact that citrus are non-climacteric fruits, or may suggest an involvement of these CsAOX genes in fruit formation more than in fruit ripening (Figs 2 and 6).…”
Section: Resultsmentioning
confidence: 99%
“…This expression trend is reminiscent of the pre-climacteric maxima of AOX transcription in non-1-MCP treated pear fruit that had undergone full conditioning [15,23]. AOX pathway activity has been shown to contribute to the respiratory climacteric during ripening in tomato, papaya, and mango [16, [24][25][26]. While GLA activated AOX, the results of this transcriptomic analysis suggest that AOX activity in 1-MCP treated pear fruit is potentially regulated in a feedforward manner as a result of carbon metabolism upstream [24,25,27].…”
Section: Glyoxylic Acid Activation Of Aoxmentioning
confidence: 99%
“…The two energy consumption systems involved, one of which was mediated by alternating oxidase (AOX) and the other by uncoupling protein (UCP), were both related to fruit maturation (Seymour et al, 2013). To illustrate this problem, Oliveira et al (2015) monitored ethylene emissions and two uncoupling (AOX and UCP) pathways during maturation of papaya (from green to yellow). The results showed that papaya was a typical respiration climacteric fruit: endogenous ethylene emissions initially increased, reached a peak at the intermediate stage of maturity, and finally returned to basic levels before maturing.…”
Section: Fruit Ripening Regulation 1regulation Of Aox and Ucp Metabomentioning
confidence: 99%